Hamstring strains: Basic science and clinical research applications for preventing the recurrent injury - Sherry, M. A.; Best, T. M.; Silder, A.; Thelen, D.; Heiderscheit, B. C. (Strength and Conditioning Journal, 2011)
Hamstring injuries occur frequently, with a high recurrence rate, in sports that require either high-speed skilled movements or excessive hip flexion with knee extension. A previous hamstring injury is the greatest risk factor for a future hamstring injury, which has led sports medicine professionals to search for improved postinjury rehabilitation strategies. Athletes may show postinjury structural changes in the muscle-tendon unit and be at risk for reinjury for up to a year after return to sport. Understanding the postinjury changes can help create practical applications for appropriate reconditioning and sports performance programs.